NOD2 reduces the chemoresistance of melanoma by inhibiting the TYMS/PLK1 signaling axis - Fang Yun; Na Wu; Xiaojia Yi; Xuedan Zhang; Yu Feng; Qinxuan Ni; Yanlong Gai; Enjiang Li; Zhe Yang; Qiao Zhang; Buqing Sai; Yingmin Kuang; et al. (Cell Death and Disease, 2024)
Abstract Nucleotide-binding oligomerization domain 2 (NOD2) is an immune sensor crucial for eliciting the innate immune responses. Nevertheless, discrepancies exist regarding the effect of NOD2 on different types of cancer. This study aimed to investigate these function of NOD2 in melanoma and its underlying mechanisms. We have validated the tumor suppressor effect of NOD2 in melanoma. NOD2 inhibited the proliferation of melanoma cells, hindering their migration and invasion while promoting the onset of apoptosis. Our study showed that NOD2 expression is closely related to pyrimidine and folate metabolism. NOD2 inhibits thymidylate synthase (TYMS) expression by promoting K48-type ubiquitination modification of TYMS, thereby decreasing the resistance of melanoma cells to 5-fluorouracil (5-FU) and capecitabine (CAP). TYMS was identified to form a complex with Polo-like Kinase 1 (PLK1) and activate the PLK1 signaling pathway. Furthermore, we revealed that the combination of the PLK1 inhibitor volasertib (BI6727) with 5-FU or CAP had a synergistic effect repressing the proliferation, migration, and autophagy of melanoma cells. Overall, our research highlights the protective role of NOD2 in melanoma and suggests that targeting NOD2 and the TYMS/PLK1 signaling axis is a high-profile therapy that could be a prospect for melanoma treatment.